Types of Conversational Maxim Flouted by the Main Characters in Green Book Movie - I Gede Suta Jaya Ambara; Ni Made Verayanti Utami; I Wayan Juniartha (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
In order to analyze further regarding to the phenomenon of flouting maxim in conversation, this study is concerned to describe the types of conversational maxim flouted by the main characters in Green Book movie through the theory of Cooperative Principle (Grice, 1975). In conducting this study, the descriptive qualitative approach is used to analyze the data. The study has found that all types of conversational maxim are flouted by the main characters in the movie, with the flouting maxim of quantity as the most dominant type in which as many as 31 (38,75%) occurences, followed by the flouting maxim of relation with 28 (35%) occurences. As for the lower ranks in the number of occurences consist of the flouting maxim of quality with 12 (15%) occurences and finally, the flouting maxim of manner with 9 (11,25%) occurences as the least dominant type of flouting maxim found in the movie. Keyword: Cooperative Principle, Flouting of Conversational Maxim, Movie